Correlation of different methods to determine the corona inception stress on overhead conductors under HVDC application - Sibanyoni, H. M. B. (Vaal University of Technology, 2022)
This dissertation’s focal point is on the correlation of different methods to determine the corona inception stress on overhead conductors under high voltage direct current (HVDC) application. The corona phenomenon is one of the key elements that should be considered when designing high voltage (HV) transmission lines. This phenomenon is known to compromise the efficiency of transmission lines and may cause electromagnetic interference (EMI) in telecommunication lines. Corona measurement methodologies form an integral part in the detection, measurement and isolation of corona discharges. The international electro-technical commission IEC 60270 specification addresses the electrical method using a coupling capacitor and acquisition unit for the detection and measurement of partial discharges. However, there are also non-conventional methods available, namely the inductive method, which uses high frequency current transformers (HFCT), acoustic methods and optical methods for detection of corona discharges (corona camera). These above-mentioned corona measurement methodologies have various advantages and disadvantages with the main difference being in the location of the sensor. The coupling capacitor is connected directly to the main circuitry of the power system, the HFCT is connected in the earth connection and the acoustic sensor as well as the corona camera being placed at a safe distance away from the system. The electrical method using a coupling capacitor is the only method that can be calibrated to measure current by means of electromagnetic coupling. The HFCT transforms the leakage current containing a frequency bandwidth flowing in the earth connection that are due to corona discharges. The corona camera visualises, locates the corona discharge point and displays the partial discharge intensity by detecting the ultraviolet radiation photon count rate. For the purpose of this dissertation, the following corona measurement methods are under review: Electrical method, inductive method and optical method. The acoustic method was not reviewed because the location of the corona measurement device is the same as that of the optical method, which is at a safe distance away from the power system. The corona measurement tests were performed in a high voltage laboratory using a corona cage. The test methodology was based on gradually increasing the voltage until the corona inception voltage is reached for both positive and negative polarities. The results show a difference in the measured inception voltage for the different methods and that the location of the corona measurement devices has an impact on the measured corona inception voltage. The results indicate that connecting the corona measurement device directly to the main circuitry of the system, as is the case with the electrical measurement method using a coupling capacitor, will be the most sensitive method and result in the lowest measured corona inception voltage.
M. Tech. (Department of Power Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Corona inception stress; Correlation; High voltage direct current (HVDC); High frequency current transformers (HFCT); Corona camera; Corona discharges; Corona measurement; Dissertations, Academic -- South Africa.; High voltages--Measurement.; Electric transformers.; Correlation (Statistics).